The Shari’ah approach to criminalise identity theft - Zulhuda, Sonny; Mohamed, Sidi Mohamed Ould (UPM Press, 2015)
Identity theft is one of the crimes that threaten both society and individuals. Millions of people have been badly affected by identity theft following misuse of their identities by criminals. The term ‘identity theft’ is used to include all illicit activities (gathering, utilising, buying selling, etc.) that target personal information (including natural and legal persons). Identity theft is not a new crime, and it has grown and become a major concern in the era of information. Around the globe, laws and regulations have been enacted and revised to accommodate the phenomenon. Based on the divine rules of Islam, the Shari’ah has its own formula and perspectives on matter such as identity theft. This paper attempts to define the term ‘identity theft’ and then recollect and examine some of the Shari’ah rules related to the crime in general and discuss their applicability to this insurmountable matter of identity theft so as to demonstrate solutions that can be offered to Muslim-populated jurisdiction. It is a doctrinal rather than empirical study, therefore, it attempts to explore the Shari’ah rules based on the primary sources of Islam, i.e. the Qur’an and the prophetic traditions (hadith), as well as the juristic opinions of prominent Muslim scholars. The study finds that the Shari’ah law is very resourceful with principles and theories on which laws on identity theft can be established. This paper demonstrates another area where the Shari’ah should be further explored to answer to the challenges of contemporary society. It is argued that a study such as this will positively contribute to the field of justice as it looks at identity crime from another approach and also suggests further research to help alleviate identity theft especially in the Muslim communities.